Preface - Dimitras, Augustinos; Mitsi, Chrysavgi; Peppas, George (International Conference on Business and Economics - Hellenic Open University, 2025)
The International Conference on Business & Economics of the Hellenic Open University (ICBE – HOU) aims to bring together leading scientists and researchers, affiliated with the HOU, to present, discuss and challenge their ideas, opinions and research findings about all disciplines of Business Administration and Economics. Additionally, the ICBE – HOU allows graduate students of all academic institutions to present, discuss and improve their research. Essentially, the Conference is an annual forum for established and new researchers as well as for practitioners in the area of Economics and Business Administration, aiming to exchange research ideas, results and useful comments on a variety of topics including accounting, marketing, taxation, finance, entrepreneurship, audit, management, social economy, etc. Moreover, ICBE – HOU supports Open Access publication. Specifically, this Conference Proceedings’ volume includes 24 articles selected among 70 papers submitted to the 10th ICBE – HOU 2024, which was successfully held on September 27-28, 2024. We followed a double-blind peer review process for the submitted papers, in which reviewers were either members of the Scientific Committee or external ones. With this fourth volume, the Conference maintains its commitment to encourage and promote high-quality works in the field of Business Administration by providing Open Access publishing. To conclude, we would like to express our gratitude to the reviewers of these manuscripts, who offered advice, suggestions and recommendations to authors. We are also extremely grateful to all authors for their excellent works and contributions to existing knowledge.